Answer:
f(6) = -10
Explanation:
Plug in 6 for x in the given equation:
f(x) = -2x + 2
f(6) = -2(6) + 2
Remember to follow PEMDAS. PEMDAS is the order of operation, and stands for:
Parenthesis
Exponents (& Roots)
Multiplication
Division
Addition
Subtraction
~
First, multiply. Note that when you are multiplying one negative number and one positive number together, your answer will be negative:
f(6) = -2(6) + 2
f(6) = (-2 * 6) + 2
f(6) = (-12) + 2
Next, simplify. Subtract:
f(6) = -12 + 2
f(6) = -10
-10 is your answer when f(6).
~